A new hypothesis may explain human parthenogenesis and ovarian teratoma: A review study - Abdelmonem Awad Hegazy; Aiman Ibraheem Al-Qtaitat; Raafat Awad Hegazy (Shahid Sadoughi University of Medical Sciences, 2023)
Abstract Parthenogenesis (PG) is a rare phenomenon occurring in humans, and understanding this may help us develop an explanation for such occurrences. Moreover, it may help reveal the cause of idiopathic ovarian teratoma (OT). We aim to explain the occurrence of PG and OT in humans based on a new hypothesis. Previous literature has been searched through relevant scientific websites and international journals on the causes and mechanisms of PG and OT in humans. The previous literature on human PG was sparse and mostly contained case reports. It appears that human PG is not as rare as previously reported but may occur spontaneously, resulting in OT formation. The difference between PG and sexual reproduction is that PG has no embryonic diversity. The biopsied embryonic samples in the PG correspond exclusively to those of the maternal side. Spontaneous PG in humans often degrades or leads to formation of OT. The cause and mechanism of spontaneous PG remain unclear in the available literature. Here, we hypothesized that in some cases the secondary oocyte and first polar body enclosed in the zona pellucida may fuse together to form a single cell that restores the diploid number of chromosomes and initiates cell division to form PG. It may go unnoticed or be represented by the OT. Future studies are recommended to investigate this hypothesis.